Specific genes of the dopaminergic (dop-3) and serotonergic (tph-1) pathways contribute to the effects of ethanol consumption in Caenorhabditis elegans - Teresa Rubio-Tomás; Cynthia A. Hunn; Gábor Hajdú; Csaba Sőti; Nektarios Tavernarakis; Csaba Barta (PLoS ONE, 2026)
Background Excessive alcohol consumption is a global health issue and a leading cause of disease, disability, and mortality. This study aimed to determine the effects of a 24-hour ethanol exposure, post-exposure withdrawal (cessation of alcohol intake), and post-exposure withdrawal relief on the sensorimotor performance of the nematode Caenorhabditis elegans . Methods A modified kinetic chemotaxis assay (commonly referred as “diacetyl race”) was conducted with worm populations subjected to three different doses of ethanol pre-exposure to assess the impact of ethanol on locomotion. Additionally, we employed lifespan, mobility, gene expression analysis and imaging assays to evaluate health status and molecular alterations occurring in the worms under different levels of ethanol exposure. Results Wild-type, dopamine receptor mutant and serotonin biosynthesis null mutant worms presented different responses to ethanol in the kinetic chemotaxis assay. Furthermore, exposure to ethanol altered vesicle exocytosis in dopaminergic and serotonergic neurons and the expression of a panel of genes associated with stress responses. Additionally, 24-hour ethanol exposure differentially influenced the lifespan of wild-type and mutant worms. Conclusions Different responses, which may be relevant to the pathogenesis of human alcohol use disorder, were observed in wild-type worms, a dopamine receptor mutant, and a serotonin biosynthesis null mutant in a variety of assays performed. Furthermore, we present a 3-step experimental model for drug tolerance, based on the well-established kinetic chemotaxis behavioral paradigm (“diacetyl race”). This model provides new insights into the effects of alcohol in worms, particularly regarding the roles of dopamine and serotonin neurotransmission. Importantly, this model holds potential for investigating the effects of other addictive substances beyond alcohol.